2010
DOI: 10.1080/0376835x.2010.508577
|View full text |Cite
|
Sign up to set email alerts
|

Local economic development in Africa: Global context and research directions

Abstract: This paper locates local economic development research and practice in Africa in a global context. It provides an overview of the international development of local economic development (LED), of its contested definitions and theoretical status, and of existing scholarship on the topic of LED policy and practice specifically across sub-Saharan Africa. Currently there is much more LED research available for South Africa than for the other sub-Saharan African countries. The paper highlights the need for this imb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 63 publications
(76 reference statements)
1
76
0
Order By: Relevance
“…Experiences from Langa and Imizamo Yethu confirm the work of some other commentators who have argued that local economic development is not inevitably widespread simply by involving local small businesses (Briedenhann & Ramchander 2006, Nel et al 2009, Rogerson & Rogerson 2010. The research reported in this paper has shed light on the dynamics which explain the limitations of promoting small businesses for local economic development in the context of developing economies.…”
Section: Resultssupporting
confidence: 76%
“…Experiences from Langa and Imizamo Yethu confirm the work of some other commentators who have argued that local economic development is not inevitably widespread simply by involving local small businesses (Briedenhann & Ramchander 2006, Nel et al 2009, Rogerson & Rogerson 2010. The research reported in this paper has shed light on the dynamics which explain the limitations of promoting small businesses for local economic development in the context of developing economies.…”
Section: Resultssupporting
confidence: 76%
“…However, at the heart of the difficulties facing these SMMEs, particularly in urban areas, are a complex of factors around their continued inability to access market opportunities, lack of access to finance/ /credit and of delivery failings in the support environment. At the sub-national level added shortcomings are disclosed in the inadequate support so far provided to SMMEs by both provincial and local levels of government across South Africa as part of 'place-based' economic development programming (Rogerson, 2007;Rogerson, Rogerson, 2010, 2012Sibanda, 2013;Rogerson, 2014). Arguably, the major achievements of the first decade of SMME support relate to the establishment of a new architecture for support of the SMME economy, which had been largely neglected throughout the apartheid era.…”
Section: Introductionmentioning
confidence: 99%
“…Rogerson and Rogerson (2010) illustrates that the LED Framework (2006) stresses that LED initiatives should promote the  "Inward investment, the SMME's development,  Investment facilitation, encouraging local business,  Improving local business investment climate,  Institutional development, improving skills and training,  Investment in business sites and premises and cluster upgrading". Pretorius and Schurink (2007) believe that the developmental initiatives taken by the local government should create an optimistic impact to the community.…”
Section: The Ward Based Led Programmentioning
confidence: 99%